The Digital Living Archive and the construction of a participatory cultural memory in the DARE-UIA project (Digital Environment for collaborative Alliances to Regenerate urban Ecosystems in middle-sized cities) - Cardoni, Giulia; Fabbri, Francesca; Iannucci, Alessandro (Bibliothecae.it, 2022)
Living Archives perform a function of social memory sharing, which contributes to building social bonds, communities, and identities. This potential lays in the ability of Living Archives to put together an archival function, which allows with the conservation and transmission of memory, with an artistic, performative and creative function linked to the present. As part of the DARE-UIA (Digital environment for colaborative alliances to regenerate urban ecosystem in middle-sized cities) project, the creation of a living digital archive made possible to create a narrative that would consolidate the cultural memory of the Darsena district of the city of Ravenna. The aim of the project is to stimulate the urban regeneration of a suburban area of a city, enhancing its cultural memory and identity heritage, through digital heritage tools. The methodology used involves various digital storytelling actions necessary for the overall narrative using georeferencing systems (GIS), storymaps and 3D reconstructions for a transversal narration of historical content such as personal and institutional historical photos and to enhance the industrial archeology heritage of the neighborhood. The aim is the creation of an interactive and replicable narrative in similar contexts to the Darsena district in Ravenna. The Living Archive, in which all the digital contents are inserted, finds its manifestation towards the outside with the form of a museum spread throughout the neighborhood, making the contents usable on smartphones via QR codes and totems inserted on-site, creating thematic itineraries spread around the neighborhood. The construction of an interactive and engaging digital narrative has made possible to enhance the material and immaterial heritage of the neighborhood by recreating the community that has historically always distinguished it.